Genotoxic effects of silver nanoparticles with/without coating in human liver HepG2 cells and in mice. Issue 6 (31st January 2019) - Wang, Xiujuan; Li, Tingzhu; Su, Xuerong; Li, Jiangyan; Li, Wenhua; Gan, Junying; Wu, Tianshu; Kong, Lu; Zhang, Ting; Tang, Meng; Xue, Yuying
Abstract: With the rapid expansion of human exposure to silver nanoparticles (AgNPs), the genotoxicity screening is critical to the biosafety evaluation of nanosilver. This study assessed DNA damage and chromosomal aberration in the human hepatoma cell line (HepG2) as well as the effects on the micronucleus of bone marrow in mice induced by 20 nm polyvinylpyrrolidone‐coated nanosilver (PVP‐AgNPs) and 20 nm bare nanosilver (AgNPs). Our results showed that the two types of AgNPs, in doses of 20‐160 μg/mL, could cause genetic toxicological changes on HepG2 cells. The DNA damage degree of HepG2 cells in 20 nm AgNPs was higher than that in 20 nm PVP‐AgNPs, while the 20 nm PVP‐AgNPs caused more serious chromosomal aberration than 20 nm AgNPs. Both kinds of AgNPs caused genetic toxicity in a dose‐dependent manner in HepG2 cells. In the micronucleus test on mouse bone marrow cells, in doses of 10, 50 and 250 mg/kg body weight administered orally for 28 days once a day, the two kinds of AgNPs have no obvious inhibitory effect on the mouse bone marrow cells, and the effect of chromosome aberration could be documented at the high dose of 250 mg/kg. These results suggest that AgNPs have genotoxic effects in HepG2 cells and limited effects on bone marrow in mice; both in vitro and in vivo tests could be of great importance on the evaluation of genotoxicity of nanosilver. These findings can provide useful toxicological information that can help to assess genetic toxicity of nanosilver in vitro and in vivo. Abstract : In present study, the genotoxicity of nanosilver was evaluated by comet assay, cytoplasmic‐block micronucleus test and mouse bone marrow micronucleus test. It was found that nanosilver could cause DNA damage and chromosomal aberration in HepG2 cells, but the results of in vivo experiments confirmed that nanosilver has few effects on the nucleus of mouse bone marrow cells.